Pengaruh Framing pada Keputusan Akuntansi Managerial dalam Perspektif Individu-Kelompok; Pengujian Empiris atas Prospect Theory dan Fuzzy-Trace Theory - Amril Arifin; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
The purposes of this study are to explore framing effects in a managerial accounting decision context on individual and group’s perspective, and to test the explanatory power of prospect theory and fuzzy-trace theory, on such effects. A number of 279 students in executive class of Magister Management Gadjah Mada University participated in this experiment. The results show the existence of the framing effect bias at individual and also at group. This result also indicates the ability of fuzzy-trace theory to predict the bias as does prospect theory, but in experiment hereinafter was designed to distinguish among the explanatory abilities of two theories in an accounting context, this result indicate that the fuzzy-trace theory provides additional power to explain the framing effect. At examination of decision difference between group and individual, result shows the existence of group polarization when information presented in gain domain/positive frame, but when information presented in loss-domain/negative-frame, individual and group do not show the existence of group polarization.